Serum fibroblast growth factor 21 levels is associated with lower extremity atherosclerotic disease in Chinese female diabetic patients - Zhang, Xiaoyan (Cardiovasc Diabetol, 2015)
BACKGROUND: Fibroblast growth factor 21 (FGF21) is an emerging metabolic regulator associated with glucose and lipid metabolism, and it is still unclear whether FGF21 is related to atherosclerosis. Here, we explored the potential link between FGF21 and lower extremity atherosclerotic disease (LEAD) in type 2 diabetic patients. METHODS: A cross-sectional study was conducted on 504 type 2 diabetic patients (283 men, 221 women). LEAD was defined by Ankle-brachial index (ABI) <0.9 and lower extremity arterial plaque evaluated by color Doppler ultrasound. Serum FGF21 concentrations were quantified by a sandwich enzyme-linked immunosorbent assay. RESULTS: The total FGF21 levels of male and female patients had no significant differenence ((299.14(177.31-534.49) vs 362.50(214.01-578.73), P=0.516). Serum FGF21 levels in LEAD group were significantly higher than non-LEAD group in females (385.34(243.89-661.54) vs 313.13(156.38-485.79), P=0.006), while not in male patients (295.52(177.09-549.64) vs 342.09 (198.70-549.87), P=0.613). In diabetic women, subjects with LEAD had significantly higher serum FGF21 regardless of non-alcoholic fatty liver disease (NAFLD) (P < 0.05). And serum FGF21 levels were positively correlated with waist circumference and systolic blood pressure after adjusted for age and BMI (r=0.198, P=0.004; r=0.152, P=0.027; respectively). Moreover, FGF21 was independently tied to femoral intima-media thickness (FIMT) (β=0.208, P=0.031). After adjusted for other LEAD risk factors, FGF21 was demonstrated to be an independent risk factor for LEAD in type 2 diabetic women (OR, 1.106; 95%CI 1.008-1.223; P=0.028). In addition, FGF21 was negatively correlated with estradiol in premenopausal diabetic women (r=−0.368, P=0.009). After adjusted for estradiol, serum FGF21 levels were still positively associated with FIMT in premenopausal diabetic women (r=0.381, P=0.007). In diabetic men, serum FGF21 levels were correlated with triglyceride and C-reactive protein even after adjusted for age and BMI (r=0.204, P=0.001; r=0.312, P < 0.001; respectively). However, serum FGF21 was not an independent impact factor for LEAD in men (P > 0.05). CONCLUSIONS: Serum FGF21 level independently and positively links LEAD in Chinese women with type 2 diabetes. The gender difference may be due to different estrogen levels.